A Study of the Validity and Reliability of the Preschool School Climate Scale (PSCS) - Ördek İnceoğlu, Seval; Aslan, Durmuş (Pedagogika, 2023)
In this study, it is aimed to psychometrically evaluate the Preschool Climate Scale (PSCS), which will evaluate the school climate characteristics of preschool education institutions. Both explanatory and confirmatory factor analyzes were performed in the sample of teachers and administrators (N=910). High internal consistency values were obtained from the structure consisting of 53 items and 6 subscales. Similar values were confirmed at different times and samples after testing. The results revealed that the PSCS is a valid and consistent scale.